Estrategias de regeneración urbana en el área de influencia de la galería central de Palmira. Barrio las Delicias (2022)
Develop urban regeneration strategies in the Palmira market square and its area of ​​influence, to mitigate the urban environmental deterioration that produces a low quality of life.